2002
DOI: 10.1002/1521-396x(200212)194:2<399::aid-pssa399>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

InGaN on SiC LEDs for High Flux and High Current Applications

Abstract: We investigate the influence of chip size, substrate shaping and mounting techniques on the light extraction efficiency of large area InGaN‐LED chips grown on 6H‐SiC substrates. New techniques to achieve good light extraction for large chip areas are demonstrated and discussed. Applying these techniques to InGaN on SiC chips with 1 mm2 size, we generate 150 mW of blue light and 33 lm of white light at a forward current of 350 mA. For efficient light extraction from the chip and for good thermal coupling the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…1-6 In particular, researchers are currently making efforts to develop highly bright LEDs for white LEDs. 7,8 To increase the efficiency of the conventional GaNbased LED, attempts have been made to change the top electrode structure and to optimize the multi-quantum well layer, by using an indium tin oxide ͑ITO͒ contact instead of the traditional thin metal to p-type contact, through surface texturing, etc. [9][10][11] However, many difficulties were encountered in the surface texturing and the formation of a transparent electrode on the p-GaN layer, in the case of the conventional GaN device having p-GaN on the top of the device, due to various problems such as the high sensitivity of p-GaN to plasma damage, the p-GaN top layer being too thin for texturing, the high contact resistance of ITO to p-GaN, etc.…”
mentioning
confidence: 99%
“…1-6 In particular, researchers are currently making efforts to develop highly bright LEDs for white LEDs. 7,8 To increase the efficiency of the conventional GaNbased LED, attempts have been made to change the top electrode structure and to optimize the multi-quantum well layer, by using an indium tin oxide ͑ITO͒ contact instead of the traditional thin metal to p-type contact, through surface texturing, etc. [9][10][11] However, many difficulties were encountered in the surface texturing and the formation of a transparent electrode on the p-GaN layer, in the case of the conventional GaN device having p-GaN on the top of the device, due to various problems such as the high sensitivity of p-GaN to plasma damage, the p-GaN top layer being too thin for texturing, the high contact resistance of ITO to p-GaN, etc.…”
mentioning
confidence: 99%
“…This CSS-LED structure consists of inclined ͕1012 ͖ stable planes that can increase the light-extraction efficiency in a similar way to the results on a GaNbased LED ATON structure through an SiC-shaping substrate process. 31 Chang et al 32 reported that the ICP-etched wavelike sidewalls mainly enhance the light output at the horizontal directions. The CSS structure has a larger sidewall surface and a better lightextraction angle on the chip sidewall that permit higher lightextraction efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…This CSS-LED structure consists of inclined {1011} stable planes and a vertical-smooth {1010} sidewall surface that can increase the light extraction efficiency in a similar way to the results of a GaN-based LEDs structure through an SiC shaping substrate process. 31 The CSS structures have a higher light extraction efficiency that was fabricated by a controllable crystallographic wet etching process immersed in a heated KOH solution. When the PL emission peak had its highest transition energy at the mesa-edge region after the controllable PEC process, the CSS-LEDs with the ever-present coneshaped structures were fabricated to have a higher light output power.…”
Section: Resultsmentioning
confidence: 99%